Digital Transformation of Media Companies in Lebanon from Traditional to Multiplatform Production: An Assessment of Lebanese Journalists’ Adaptation to the New Digital Era - El Takach, Ali; Nassour, Farah; Hejase, Hussin Jose (Žurnalistikos tyrimai, 2023)
This research aims to assess Lebanese media organizations’ and journalists’ readiness and adaptation to the new digital era requirements. Journalism has always been affected by technology. Adopting new information and communications technology has obliged changes in journalistic practices and led to new business models and journalistic practices. For example, implementing Newsroom Computer Systems (NRCs) in media companies has led to radical changes in the departments of these organizations, and in particular in the newsrooms. The journalists in newsrooms are the human factor that is considered an essential element in this change. It touched on the depths of productivity and the mode of journalistic work. In the new era of media convergence, journalists are called upon to follow this trend (modern journalism) and become more versatile, where their work becomes streamlined and redesigned. The new and more flexible journalistic practices emerging in newspaper and television production, in combination with online journalism, have a profound effect on the role of journalists and their competencies requirements. Having multi competencies is explained by mastering the basic rules (writing, etc.) in the journalism profession and digital knowledge related to this profession (visualizing data, using the digital tools necessary for work, etc.). This study uses quantitative, descriptive, and deductive approaches supported by a structured survey questionnaire. The sample in this research constituted 96 respondent journalists selected conveniently. Data were analyzed descriptively and reported in charts for clarity. Results show that from an overall analysis, Lebanese media organizations and journalists are moderately prepared to deal with the digital era requirements. Most of the research variables scored between 40 to 50% in terms of preparedness and functionality during the digital transformation era. The research implications show that in Lebanon, as elsewhere in the media industry, the human factor’s digital culture plays an essential role in the advancement of the companies towards the digital environment. In the Lebanese organizations’ case, the economic and monetary crisis factors besides the human factor, have affected the technical implementation and the digital transformation of the media outlets. In this media landscape, the role of academic institutions (i.e., universities and research centers) must be proactive to define the new set of digital and journalistic skills required and needed to enhance the transformation towards the digital multitasking and cross-platform profiles needed to adopt the digital mindset effectively and efficiently.